Enhanced Survival of Lactobacillus Lg71 from Mangrove Sediment Under Simulated Gastric and Intestinal Conditions - Kusharyati, Dyah Fitri; Satwika, Taruna Dwi; Alfisah, Rizal Khoirun; Mariana, Afifah; Rovik, Anwar; Oedjijono, Oedjijono (Universitas Karya Husada Semarang, 2026)
Background: For a probiotic to offer health benefits, it must stay viable through the tough environment of the human gastrointestinal tract. This study assesses the effectiveness of sodium alginate encapsulation in improving the survival of Lactobacillus LG71, a new strain from mangrove sediment, under simulated gastric and intestinal conditions. Objective: This study aims to evaluate the effectiveness of sodium alginate encapsulation in enhancing the viability and survival of Lactobacillus LG71, a probiotic strain isolated from mangrove sediment, during cold storage and under simulated gastric and intestinal conditions. Methods: Lactobacillus LG71 was encapsulated in sodium alginate beads. The viability of both encapsulated and free (non-encapsulated) cells was assessed over a 4-week storage period at 4 °C and during sequential exposure to simulated gastric and intestinal environments. Results: Encapsulation significantly improved survival rates compared to free cells (p < 0.05). Although both groups experienced a decline during the first week of storage, encapsulated cells maintained a high viability of approximately 107 CFU/mL, losing only 2.51 log CFU/g over four weeks. Most notably, encapsulated Lactobacillus LG71 demonstrated greater resilience during digestion, retaining populations of 2.21 log CFU/mL in gastric simulations and 1.00 log CFU/mL in intestinal simulations. In contrast, free cells were much more vulnerable to these acidic and enzymatic conditions. Conclusion: Sodium alginate encapsulation effectively protects Lactobacillus LG71 from environmental and biological stressors. These findings indicate that encapsulation is a crucial step for the commercial application of mangrove-derived probiotics, ensuring that a viable dose of living cells reaches the host's lower gastrointestinal tract to promote health benefits.